Two Murders Involving the Dismemberment of Corpses in the Same Family : – Female Offender and Death Penalty - Péter, Dulai (Magyar Rendészet, 2025)
Introduction: There are a growing number of sources available to researchers about the perpetrators of crimes sentenced to death for public offences committed during the Kádár Regime. However, very little information is available on the assessment of pardon applications and the justification for commuting sentences. Aim: The aim of the study is to give an idea of the jurisprudence of the period, the role of public opinion and the difficulties of research by presenting a unique case in criminology, criminalistics and criminal law. Methodology: I present the case of the woman who, with the help of her husband, murdered one of her sons called József, and several years later, she murdered her husband with the help of her other son called László using the documents still available, press reports and forensic studies of the crime referenced by professionals. Results: The perpetrator was not executed, but was pardoned and her sentence was commuted to a fixed term of imprisonment. However, the public could not have known this; this information comes from the sources I have analysed that are not public. Conclusion: The most important lesson to be learned from the court proceedings in this case is that although the person sentenced to death was granted clemency, the public was not informed of this as the press was not allowed to publish this information. The primary reason for this might have been fear of the expected public outcry. This kind of social pressure most surely influenced the work of the police and the law enforcement agencies. To confirm or refute this, several criminal cases with similar decisions should be examined to gain a better understanding of the practice at the time.